2017
DOI: 10.1038/cdd.2017.126
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the etiological therapy of cystic fibrosis

Abstract: Etiological therapies aim at repairing the underlying cause of cystic fibrosis (CF), which is the functional defect of the cystic fibrosis transmembrane conductance regulator (CFTR) protein owing to mutations in the CFTR gene. Among these, the F508del CFTR mutation accounts for more than two thirds of CF cases worldwide. Two somehow antinomic schools of thought conceive CFTR repair in a different manner. According to one vision, drugs should directly target the mutated CFTR protein to increase its plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 180 publications
1
43
0
5
Order By: Relevance
“…5C). CFTR modulators demonstrated that direct repair of the malfunctioning protein can partly restore normal lung function [188]. However, this treatment requires continuous pharmacological intervention.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…5C). CFTR modulators demonstrated that direct repair of the malfunctioning protein can partly restore normal lung function [188]. However, this treatment requires continuous pharmacological intervention.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Loss-of-function mutations of CFTR cause the most frequent human monogenetic lethal disease, cystic fibrosis (CF). 1 The pathogenesis of CF involves two complementary phenomena. On one hand, failure to transport chloride anions into the extracellular space increases the viscosity and thickness of mucus, hence compromising its elimination from the respiratory tract (which facilitates chronic inflammation coupled to recurrent pulmonary infections) and the pancreatic ducts (which drives failure of the exocrine pancreas and consequent nutrient malabsorption).…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr)mentioning
confidence: 99%
“…On one hand, failure to transport chloride anions into the extracellular space increases the viscosity and thickness of mucus, hence compromising its elimination from the respiratory tract (which facilitates chronic inflammation coupled to recurrent pulmonary infections) and the pancreatic ducts (which drives failure of the exocrine pancreas and consequent nutrient malabsorption). 1 On the other hand, imbalances in intracellular anion fluxes (perhaps combined with deficient CFTR scaffold functions) favor a progressive and irreversible imbalance in proteostasis due to activation of transglutaminase 2 (TGM2) and reduced beclin 1 (BECN1) expression, culminating with inhibition of autophagy. [1][2][3][4] These three phenomena (deficient CFTR function, TGM2 activation, and autophagy impairment) amplify each other in a feed-forward circuitry, locking affected cells in a close-to-irrevocable proinflammatory state that contributes to disease pathogenesis.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr)mentioning
confidence: 99%
See 1 more Smart Citation
“…A FC possui um caráter multissistêmico, apresentando um quadro clínico variável e com grande diversidade na gravidade e na evolução clínica (ARIAS LLORENTE; BOUSOÑO GARCÍA; DÍAZ MARTÍN, 2008;WELSH et al, 2001). O fenótipo da FC inclui a elevação de eletrólitos no suor e pode compreender insuficiência pancreática (IP), doenças gastrointestinais e hepatobiliares, além de infertilidade masculina (MAIURI; RAIA; KROEMER, 2017, ROSA et al, 2018.…”
Section: Introductionunclassified